2022
DOI: 10.1038/s41598-022-07555-z
|View full text |Cite
|
Sign up to set email alerts
|

Virtual simulation of the biomechanics of the abdominal wall with different stoma locations

Abstract: An ostomy is a surgical procedure by which an artificial opening in the abdominal wall, known as a stoma, is created. We assess the effects of stoma location on the abdominal wall mechanics. We perform three-dimensional finite element simulations on an anatomy model which was generated on the basis of medical images. Our simulation methodology is entirely based on open source software. We consider seventeen different locations for the stoma incision (trephine) and we simulate the mechanical response of the abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The present geometry model, illustrated in Fig. 1 , is similar to the one used in our previous work 5 . It consists of external oblique (EO), internal oblique (IO), rectus abdominis (RA) and transverse abdominis (TR) muscles, as well as the linea alba (LA), which was considered with standard dimensions of 2 cm (i.e., without rectus diastasis) 12 .…”
Section: Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present geometry model, illustrated in Fig. 1 , is similar to the one used in our previous work 5 . It consists of external oblique (EO), internal oblique (IO), rectus abdominis (RA) and transverse abdominis (TR) muscles, as well as the linea alba (LA), which was considered with standard dimensions of 2 cm (i.e., without rectus diastasis) 12 .…”
Section: Models and Methodsmentioning
confidence: 99%
“…Following our previous work 5 we assumed a linear elastic behavior of the AW tissues, where σ is the stress tensor, ε is the strain tensor, accounting for the relative deformation of tissues, and E is the elastic modulus. The specific E values for each tissue, together with the bibliographic source, are listed in Table 2 .…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FEM has been used to examine the constitutive behaviour of various tissues in the AW 5 . More recently, holistic models based on FEM have been developed to simulate the biomechanics of AWs subjected to local weaknesses in various locations seeking to address challenging scenarios of hernia development [6][7][8][9] . For example, Tuset et al 9 concluded that intestinal stoma location has no significant impact on the resulting stress and strain distributions except when it is located in the linea alba.…”
mentioning
confidence: 99%
“…More recently, holistic models based on FEM have been developed to simulate the biomechanics of AWs subjected to local weaknesses in various locations seeking to address challenging scenarios of hernia development [6][7][8][9] . For example, Tuset et al 9 concluded that intestinal stoma location has no significant impact on the resulting stress and strain distributions except when it is located in the linea alba. As a predictive modelling tool, FEM can complement clinical research and facilitate the surgeons' decisions.…”
mentioning
confidence: 99%